CCDC154 knockdown inhibits growth of liver cancer via suppressing expression of Snail - Rulan Ma; Hongmei Nie; Caijing Mo; Dawei Yuan; Kun Zhu; Kang Li (European Journal of Medical Research)
Abstract Objective The effect of coiled-coil domain-containing 154 (CCDC154) in liver cancer (LC) remains unexplored. The objective of this study was to investigate the role of CCDC154 in LC and its underlying mechanism. Methods The analysis of CCDC154 expression and prognosis was performed using UALCAN, Human Protein Atlas and Kaplan–Meier plotter websites. Protein expression was measured using Western blotting assay. Lentivirus was used to silence CCDC154 expression in LC cells. The proliferation and apoptosis of LC cells was evaluated by cell counting assay, colony formation assay and flow cytometry. The migration and invasion of LC cells were investigated using scratch wound-healing assay and Transwell assay. Results The results showed that CCDC154 was highly expressed in LC and related to tumor grade and stage. High CCDC154 expression was associated with to poor outcomes in LC patients. Silencing of CCDC154 inhibited proliferation, migration and invasion of LC cells. It also increased apoptosis in LC cells. After CCDC154 knockdown, the expression of Twist, Vimentin and Snail was down-regulated. Overexpression of Snail abated the inhibitory caused by CCDC154 knockdown on LC cell growth. Conclusion CCDC154 knockdown suppressed LC development through reducing Snail expression.